The influence of screw type, alloy and cylinder position on the marginal fit of implant frameworks before and after laser welding Influência do tipo de parafuso, liga e da posição do cilindro na adaptação marginal das infra-estruturas sob implantes antes e após a soldagem a laser - Daniela Castilio; Ana Paula Ribeiro do Vale Pedreira; Paulo Henrique Orlato Rossetti; Leylha Maria Nunes Rossetti; Wellington Cardoso Bonachela (University of São Paulo, 2006)
Misfit at the abutment-prosthetic cylinder interface can cause loss of preload, leading to loosening or fracture of gold and titanium screws. OBJECTIVES: To evaluate the influence of screw type, alloy, and cylinder position on marginal fit of implant frameworks before and after laser welding. METHODS: After Estheticone-like abutments were screwed to the implants, thirty plastic prosthetic cylinders were mounted and waxed-up to fifteen cylindrical bars. Each specimen had three interconnected prosthetic components. Five specimens were one-piece cast in titanium and five in cobalt-chromium alloy. On each specimen, tests were conducted with hexagonal titanium and slotted gold screws separately, performing a total of thirty tested screws. Measurements at the interfaces were performed using an optical microscope with 5mm accuracy. After sectioning, specimens were laser welded and new measurements were obtained. Data were submitted to a four-way ANOVA and Tukey's multiple comparisons test (alpha=0.05). RESULTS: Slotted and hexagonal screws did not present significant differences regarding to the fit of cylinders cast in titanium, either in one-piece casting framework or after laser welding. When slotted and hexagonal screws were tested on the cobalt-chromium specimens, statistically significant differences were found for the one-piece casting condition, with the slotted screws presenting better fit (24.13µm) than the hexagonal screws (27.93 µm). Besides, no statistically significant differences were found after laser welding. CONCLUSIONS: 1) The use of different metal alloys do exert influence on the marginal fit, 2) The slotted and hexagonal screws play the exclusive role of fixing the prosthesis, and did not improve the fit of cylinders, and 3) cylinder position did not affect marginal fit values. A desadaptação na interface abutment-cilindro protético pode causar perda da pré-carga, levando ao afrouxamento ou fratura dos parafusos de ouro e titânio. OBJETIVOS: Avaliar a influência do tipo de parafuso, liga e posição do cilindro na adaptação marginal de infra-estruturas sobre implante antes e após a soldagem a laser. MÉTODOS: Após os abutments do tipo Estheticone serem aparafusados nos implantes, trinta cilindros protéticos de plástico foram montados e encerados com 15 barras cilíndricas. Cada espécime possuía três componentes protéticos interconectados. Cinco espécimes foram fundidos em monobloco com liga de titânio e liga de cobalto-crômio. Em cada espécime, os testes foram conduzidos com parafusos hexagonais de titânio e com parafusos de ouro com fenda, separadamente, num total de 30 parafusos testados. As medidas nas interfaces foram feitas com microscópio óptico com 5mm de precisão. Após o seccionamento, os espécimes foram soldados a laser e novas medidas obtidas. Os dados foram submetidos para análise com os testes ANOVA a quatro critérios e Tukey para comparações múltiplas (alfa=0,05). RESULTADOS: Os parafusos com fenda e hexágono não apresentaram diferenças significantes independente da adaptação dos cilindros fundidos em titânio, tanto em monobloco como após a soldagem a laser. Quando os parafusos com hexágono e fenda foram testados nos espécimes de cobalto-crômio, diferenças estatisticamente significantes foram encontradas na condição monobloco, com os parafusos fendidos apresentando melhor adaptação (24,13µm) do que os com hexágono (27,93 µm). Além disso, nenhuma diferença significante foi encontrada após a soldagem a laser. CONCLUSÕES: 1) O uso de diferentes ligas metálicas exerce influência nos resultados, 2) Os parafusos com hexágono e fenda somente possuem o papel de fixar a prótese, e não melhoram a adaptação dos cilindros e 3) a posição do cilindro não afetou os valores de adaptação marginal.